2016
DOI: 10.3389/fimmu.2016.00322
|View full text |Cite
|
Sign up to set email alerts
|

Transient Migration of Large Numbers of CD14++ CD16+ Monocytes to the Draining Lymph Node after Onset of Inflammation

Abstract: The dynamics of skin-draining cells following infection or vaccination provide important insight into the initiation of immune responses. In this study, the local recruitment and activation of immune cells in draining lymph nodes (LNs) was studied in calves in an adjuvant-induced inflammation. A transient but remarkably strong recruitment of monocytes was demonstrated after onset of inflammation, constituting up to 41% of live cells in the draining LNs after 24 h. Numerous CD14+ cells were visualized in subcut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Plasma from diseased animals induced an elevated expression of genes encoding for the inflammatory mediators CXCL8, CXCL1 , and IL1B in intM ( 90 ). The clinical relevance of bovine intM as a pro-inflammatory monocyte with an important role during the acute phase of inflammation has been confirmed in a recent work on calves with adjuvant-induced skin inflammation ( 91 ). The study has demonstrated a potent recruitment of bovine intM to the draining lymph node after the onset of a local skin inflammation with upregulated genes for pro-inflammatory cytokines.…”
Section: Clinical Relevance Of Bovine Monocyte Subsetsmentioning
confidence: 84%
“…Plasma from diseased animals induced an elevated expression of genes encoding for the inflammatory mediators CXCL8, CXCL1 , and IL1B in intM ( 90 ). The clinical relevance of bovine intM as a pro-inflammatory monocyte with an important role during the acute phase of inflammation has been confirmed in a recent work on calves with adjuvant-induced skin inflammation ( 91 ). The study has demonstrated a potent recruitment of bovine intM to the draining lymph node after the onset of a local skin inflammation with upregulated genes for pro-inflammatory cytokines.…”
Section: Clinical Relevance Of Bovine Monocyte Subsetsmentioning
confidence: 84%
“…The major CD14 high CD16 neg classical monocyte population is rapidly recruited to sites of inflammation or tissue damage, while the less-frequent CD14 low CD16 high non-classical monocytes exhibit vascular surveillance functions during steady state. The CD14 high CD16 dim “intermediate” monocytes [ 14 ] are the least abundant monocyte population, although their abundance can vary in pathological conditions [ 15 ]. Recent studies of gene expression profiles of the monocyte subsets [ 16 18 ] and of their kinetics in blood [ 19 ] have shown that the monocyte population in blood is a developmental continuum.…”
Section: Isolation and Characterization Of Major Mdsc Types From Perimentioning
confidence: 99%
“…They are known as a heterogeneous group of cells consisting of multiple subsets generated through distinct developmental pathways with diverse functional specializations 3 . Human monocytes consist of phenotypically and functionally distinct subpopulations, a varying amount of which is observed in the blood of patients in numerous pathological states, such as infections, autoimmune diseases, respiratory and cardiovascular diseases and inflammatory disorders 4,5 . During homeostasis and under pathological conditions, each subpopulation may play a different role.…”
Section: Introductionmentioning
confidence: 99%